Geography and Communal Conflict in Indonesia - Sujarwoto Sujarwoto (Indonesian Journal of Geography, 2017)
The determinants of communal conflicts in Indonesia have been widely documented. However, most of them ignore geographical aspects of communal conflicts. This paper examines geographical determinants of communal conflicts in Indonesia. Data comes from the 2008 Village Potential Census (Podes) and official statistics which consist of communal conflict information across all Indonesia’s districts (N districts = 465). Results from spatial dependent model show that communal conflict to be spatially dependent through latent determinants, meaning that communal conflict clusters because of clustering of latent determinants within district. Rather than religious and ethnic heterogeneity, communal conflict is positively associated with poverty, economic inequality, elite capture, and weak capacity of districts to manage fiscal resources.